Criminalisation of copyright piracy and international trade : a marriage of convenience? the case with transpacific partnership agreement - Abdul Ghani Azmi, Ida Madieha (2016)
The signing of the Transpacific Partnership Agreement (TPPA) between twelve member countries, with Malaysia included, has set a new, higher benchmark for copyright enforcement. In three ways, the landscape of copyright law has been changed significantly. First, TPPA expand the coverage of the kinds of Intellectual Property recognised. Secondly, what constitute copyright violations has been expanded. Thirdly, sanctions for copyright piracy has been made tougher and sentencing lengths for such piracy has been lengthened. The usage of trade agreements to compel countries to improve copyright domestic policy is not a new strategy. The antecedent to TPPA is the TRIPs Agreement that was concluded on the basis that copyright piracy and counterfeiting has grown from just mere domestic nuisance to an effective barrier to free trade. This paper addresses the TPPA and analyses the rationale to the introduction of more stringent measures under TTPA. It seeks to understand the shift in the discourse of the policy makers regarding the 'severity' of copyright offences. It examines questions such as to what extent should copyright infringement be criminalised? Even if it is criminalised, why must it be imposed with more severe penalties than an ordinary economic crime?